Perlindungan Hukum terhadap Investor terhadap Manipulasi Laporan Keuangan Perusahan Tbk - Randi Nurprastyo (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Financial reports are a crucial instrument in the business and investment world, as they provide information that reflects a company's financial condition. Accuracy and timeliness in the presentation of financial reports enable management to make data-driven strategic decisions while providing a transparent picture to stakeholders, including investors. Investors generally use financial reports as a basis for assessing an issuer's performance and prospects before making investment decisions. However, in practice, many companies manipulate financial reports to project better performance than reality. Worse, these manipulative actions sometimes involve external auditors, who should be independent and objective. Financial report manipulation can result in significant losses for investors who have invested their capital based on advertised information. Therefore, legal protection for investors is crucial in maintaining public trust in the capital market. This legal protection can take the form of administrative action by the Financial Services Authority (OJK), criminal sanctions for perpetrators of manipulation under the Capital Markets Law, and civil lawsuits by aggrieved investors. Furthermore, the role of whistleblowers and a transparent reporting system are also supporting instruments in uncovering violations. Enforcing regulations and overseeing accountability for financial reporting is essential to creating a healthy, fair, and sustainable investment climate in Indonesia. In addition to reactive legal protection, preventive measures are also crucial to prevent financial report manipulation. This can be achieved through improving the quality of good corporate governance, strengthening the internal audit function, and enforcing ethical standards for the public accounting profession. Companies also need to implement technology-based financial reporting systems that are integrated and auditable in real time to enhance transparency.